Ionospheric response to the February 27, 2023 intense geomagnetic storm over Kharkiv and the Akademik Vernadsky station - Reznychenko, Maryna; Kotov, Dmytro; Bogomaz, Oleksandr; Zhivolup, Taras; Reznychenko, Artem; Zalizovski, Andriy; Koloskov, Oleksandr; Lisachenko, Volodymyr; Dzyubanov, Dmytro (Ukrainian Antarctic Journal, 2024)
This study aims to investigate ionospheric responses to the February 27, 2023 intense geomagnetic storm over Kharkiv and the Akademik Vernadsky (hereinafter – Vernadsky) station using ionosondes. The behavior of the key ionospheric parameters (hmF2 and NmF2) before, during, and after the geomagnetic storm was investigated. The observational F2-layer peak electron density and height were compared with those derived by the International Reference Ionosphere (IRI-2016) model. Significant negative ionospheric storms were identified over Kharkiv during all the nights after the geomagnetic storm beginning (up to 70% decrease of the NmF2). At the same time, during the daytime hours of February 27, a moderate positive ionospheric storm (up to 40% increase of the NmF2) was registered. Over Vernadsky Station, during the main phase of the geomagnetic storm, a very strong negative ionospheric storm (up to a factor of 4 reduction of the NmF2) was observed both during daytime and night-time. We offer hypotheses of the possible physical mechanisms (electrodynamics, changes in the neutral composition, partial depletion of the plasmasphere, and a shift of the ionospheric trough) responsible for the observed ionospheric effects. Further investigations with physical models of the coupled atmosphere, ionosphere, and plasmasphere are necessary to identify the dominant drivers in each case. Comparison of the observed ionospheric parameters with the predictions of IRI F2-layer peak sub-models shows that neither hmF2 (AMTB-2013 and SHU-2015), and NmF2 (URSI and CCIR) sub-models can qualitatively reproduce strong storm-induced ionospheric variations over Kharkiv. Over Vernadsky Station, both hmF2 sub-models underestimate the observed hmF2 during the storm period, whereas the NmF2 sub-models are more sensitive to the changes in geomagnetic activity. Under geomagnetically quiet conditions, the qualitative agreement between observations and the model is satisfactory, but further improvements of the empirical models are required to reach acceptable accuracy of quantitative predictions.